Unconventional politics of unconventional gas: environmental reframing and policy change - Kear, Andrew Robert, author; Duffy, Robert J., advisor; Davis, Charles E., committee member; Saunders, Kyle L., committee member; Stednick, John D., committee member (Colorado State University. Libraries, 2011)
The present Rocky Mountain West natural gas boom, enabled by historic pro-resource-development political, institutional, economic, and cultural structures, is a politically contested battle over values. Volatile political action, unconventional coalitions, and unconventional politics engulf this unconventional gas boom - especially at the state level. In this comparative case study of natural gas policy in Wyoming, Colorado, and New Mexico, I measure and compare these values, expressed as frames, through textual analysis of interest group public documents and state legislative bills and statutes from 1999-2008. By developing a new measure of state legislative framing, I test the relationship between interest group and institutional framing and also provide a viable measure of policy change useful to Narrative Policy Analysis theory. Results show that competing interest group and state legislative framing efforts are dynamic, measurably different, and periodically correlative. Competing interest groups rarely engage each other, except as the conflict matures when status-quo-supporters break their silence and engage the challengers' frames that have gained legislative traction. Environmental and land-use counter-framing ensues, but status-quo-supporters remain vigilant in their economic framing. Economic frames retain their institutional privilege within Wyoming and New Mexico, but natural gas policy undergoes a complete environmental reframe in the Colorado state legislature. Although the historically dominant economy frame based on "Old West" values remains largely intact, the respective state legislatures partially reframe policy (within 4 years) using environment, alternative land-uses, and democracy frames based on "New West" and long-extant but previously marginalized status-quo-challenger definitions. This reframing is not a strictly partisan issue, but rather it is influenced by political context, policy diffusion, and long-term interest group advocacy and framing efforts. A policy punctuation is observed in state legislative reframing and by the passage of three status-quo-challenging statutes in Wyoming (2005), four in Colorado (2007), and one in New Mexico (2007). Policy reframing, although rare in most policy areas, is common during this natural gas policy punctuation. The politics of successful reframing is the politics of punctuation.
Keywords: energy; environment; natural gas; policy change; policy punctuation; reframing